Instructional Leadership Expenditures at Texas Schools: A Multiyear, Statewide Analysis - Tania M. Merik; John R. Slate (UMT Education Review, 2022)
This study was conducted to determine the degree to which differences were present in the distribution of Instructional Leadership dollars spent per student at the elementary, middle, and high school levels for the 2009-2010 through the 2018-2019 school years in Texas. Texas statewide data for all public schools were obtained from the Texas Education Agency. Because archival data were analyzed, a causal-comparative research design was present. To determine whether statistically significant differences were present in Instructional Leadership dollars spent by school level, inferential statistical procedures were calculated for each school year. Statistically significant differences were established for each school year.  The amount of Instructional Leadership dollars spent per pupil were highest at the high school level, followed by the middle school level, and were lowest at the elementary school level.  From the 2009-2010 school year through the 2018-2019 school year, expenditures for elementary, middle, and high schools across the State of Texas increased by only $42, $40, and $48, respectively. As such, the Instructional Leadership funding did not keep up with the rate of inflation in this time period.Implications and recommendations for future research were discussed.